2016
DOI: 10.1515/rehab-2015-0053
|View full text |Cite
|
Sign up to set email alerts
|

Using smartphones in the evaluation of spinal curvatures in a sagittal plane

Abstract: Introduction: In physiotherapeutic diagnostic processes, various tools and methods may be used. However, price and availability may limit their daily use in clinical practice. Therefore, the suggestion that smartphones with specific applications may be useful as diagnostic tools can be found in the literature. However, before using them in clinical practice, it is important to verify their reliability. The aim of the study was to evaluate the consistency of measurements of the curvatures in the sagittal plane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In terms of intra-rater reliability, measurements made using the smartphone application had excellent reliability in children with CP (ICC=0.81-0.98). Was et al (20) also found that thoracic kyphotic curve assessment with a smartphone application exhibited excellent reliability (ICC=0.80) in 40 healthy adults. Similarly, Furness et al (21) demonstrated that measuring thoracic rotation range of motion with a smartphone application had excellent intra-(ICC=0.94-0.98) and inter-rater reliability (ICC=0.72-0.89).…”
Section: Discussionmentioning
confidence: 96%
“…In terms of intra-rater reliability, measurements made using the smartphone application had excellent reliability in children with CP (ICC=0.81-0.98). Was et al (20) also found that thoracic kyphotic curve assessment with a smartphone application exhibited excellent reliability (ICC=0.80) in 40 healthy adults. Similarly, Furness et al (21) demonstrated that measuring thoracic rotation range of motion with a smartphone application had excellent intra-(ICC=0.94-0.98) and inter-rater reliability (ICC=0.72-0.89).…”
Section: Discussionmentioning
confidence: 96%
“…[66] Scoliosis [67] Rib Hump Angle/Scoliosis [68] Kyphotic Angles [69] Cobb Angle/Thoracic Scoliosis [70] Cobb Angle/Thoracic Scoliosis [71] Lumbar Lordosis [72] Rib Hump Angle/Scoliosis Evaluation [73] Cobb Angle of Thoracolumbar Scoliosis [74] Cobb Angle [75] Cobb Angle [76] Cobb Angle [77] Head, Ribcage, Shoulder, Hip and Knee Tilt [65] Inclination of the Human Spinal Points [78] SS and Lumbar Curve [79] PI, PT and LL [80] Sagittal Curvaures [81] Thoracic Spine Rotation [82] LL, PI, and PT [83] Head, Ribcage, Shoulder, Hip Tilt [84] Head, Ribcage, Shoulder, Hip Inclination [85] Scoliosis Angle [86] Head, Shoulder and Ribcage Tilt [87] Head, Ribcage, Shoulder, Hip and Knee Tilt [88] LL, PI, SS and PT [89] LL, PT, and SS [90] Rib Hump/Scoliosis Evaluation Note: LL = Lumbar Lordosis; PI = Pelvic Incidence; SS = Sacral Slope; PT = Pelvic Tilt.…”
Section: Study Measures Takenmentioning
confidence: 99%
“…The Scoliometer 1.1 is another method that requires the smartphone to be positioned directly on the patient's back (free standing position and free sitting position) to determine the degrees of kyphosis and lordosis of the spine. In the study of Waś et al [80], the smartphone with Scoliometer 1.1 application is positioned at the levels of the cervicothoracic junction (C7-T1), in the thoracic segment (T6-T7), at the thoracolumbar junction (T12-L1) and at the lumbosacral junction (L5-S1) to measure lumbar lordosis angle, upper and lower thoracic kyphosis angle. A similar process is performed by Koumantakis et al [78] by marking the spinous processes of T12-L1 and S1-S2 to assess the lumbosacral parameters.…”
Section: Study Measures Takenmentioning
confidence: 99%
“…The reliability and validity studies were conducted on the use of smartphone applications for measuring range of motion of different joints (16)(17)(18). In addition, the reliability and validity of smartphone applications to measure thoracic kyphosis angle were investigated (19,20); however, the reliability and validity of a measurement instrument are not enough for an interpretation of change scores, the standard error of measurement (SEM) and the minimal detectable change should be determined (21). A smaller SEM is an indicator of a good reproducibility (22).…”
Section: Introductionmentioning
confidence: 99%